Herodotus and Hellenistic culture : literary studies in the reception of the Histories - Priestley, Jessica (Oxford University Press, 2014)
In a series of literary studies, Priestley explores some of the earliest ancient responses to Herodotus' 'Histories' through the extant written record of the early and middle Hellenistic period. Responses to the Histories were rich and varied, and the range of Hellenistic writers responding in different ways to Herodotus' work is in part a reflection of the 'Histories 'own broad scope. The 'Histories' remained relevant in this later age and continued to speak meaningfully to a broad range of readers long after Herodotus' death. This book explores a variety of discourses where Herodotus occupies an important place in the intellectual background, and, in particular, it draws attention to writers not usually categorized as historians in order to broaden our perspectives on Herodotus' cultural importance.